2020
DOI: 10.1002/jcb.29709
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0011269 sponges miR‐122 to regulate RUNX2 expression and promotes osteoporosis progression

Abstract: Circular RNAs (circRNAs) are a novel class of noncoding RNAs that are widely expressed in human disease. However, circRNAs expression profile and potential mechanism in osteoporosis pathogenesis remain to be further studied. In the present study, a total of 69 circRNAs were identified to be abnormally expressed in osteoporosis patient samples by microarray and bioinformatics analyses. We found that circ_0011269 was notably downregulated in osteoporosis (fold change, 3.94). By means of miRanda algorithm, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…RUNX2, a key determinant of osteoblast differentiation and maturation (75), is broadly used as an osteogenic marker gene. Xu et al showed that the expressions of circ_0011269 and RUNX2 were both upregulated, while the expression of miR-122 was downregulated during the osteogenic process (45). A subsequent study showed that circ_0011269 sequestered miR-122 to regulate the expression level of RUNX2.…”
Section: Runxmentioning
confidence: 99%
“…RUNX2, a key determinant of osteoblast differentiation and maturation (75), is broadly used as an osteogenic marker gene. Xu et al showed that the expressions of circ_0011269 and RUNX2 were both upregulated, while the expression of miR-122 was downregulated during the osteogenic process (45). A subsequent study showed that circ_0011269 sequestered miR-122 to regulate the expression level of RUNX2.…”
Section: Runxmentioning
confidence: 99%
“…The majority of osteoporosis -related circRNAs are involved in regulating osteogenesis by sponging miRNAs and consequently regulating the expression or activity of downstream osteogenesis genes. Circ-RUNX2 88 , circ-VANGL1 89 , circ-0011269 90 , circ-0076906 91 , circRNA-0016624 92 , circ-0006393 93 , circRNA-0048211 94 , circ-SLC8A1 95 , circ-YAP1 96 and circ-0076690 97 are found down-regulated in osteoporosis and could enhance osteogenesis of BMSCs by sponging miRNAs and subsequently upregulating the expression and activities of osteogenetic genes (such as RUNX2, BMP2, OPN, OCN, OGN, FOXO1, APAK2 or ALP) ( Figure 4 A ). Exosomes of BMSCs (BMSCs-Exos) have also been shown to function in bone regeneration 98 - 100 , while exosomes-derived from circ-Rtn4 have been shown to promote osteogenesis by targeting miR-146a 101 .…”
Section: Circrnas and Osteoporosismentioning
confidence: 99%
“…mir-183-5p inhibits BMSC proliferation and bone formation, as well as promotes osteoclast differentiation in BM-derived macrophages via the co-oxygenase-1 (Ho1) target, suggesting that miR-183 by effect is involved in the absorption of both, in reducing age-related bone in absorption processes. 131 Vesicular miR-31 targets Fzd3, a Wnt5a receptor and prevents osteogenic differentiation. 132 miR-214, another age-related miRNA, is increased with age in bone.…”
Section: Mirnas In Opmentioning
confidence: 99%